2015
DOI: 10.1111/apa.13009
|View full text |Cite
|
Sign up to set email alerts
|

Using axillary temperature to approximate rectal temperature in newborns

Abstract: Although it is possible to construct a formula that estimates neonate rectal temperature based on axillary temperature with a slightly higher reliability than simply adding a fixed value like 0.4°C, such a formula would be too complex to apply in practice. Adding 0.3°C or 0.4°C to the measured axillary temperature for premature infants or full-term infants, respectively, yields acceptable approximations in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Third, body temperature was not collected using uniform methods, and we did not register the site at which the temperature was measured, which might have influenced the precision of the temperature. Recent studies have shown differences between axillary and rectal measurements but have also indicated that the differences are smaller in infants of younger gestational ages [29-32]. Fourth, 243 infants (5.2%) had missing admission temperatures, and 300 infants (6.4%) were excluded due to transfer to other hospitals, which could have potentially biased the results.…”
Section: Discussionmentioning
confidence: 99%
“…Third, body temperature was not collected using uniform methods, and we did not register the site at which the temperature was measured, which might have influenced the precision of the temperature. Recent studies have shown differences between axillary and rectal measurements but have also indicated that the differences are smaller in infants of younger gestational ages [29-32]. Fourth, 243 infants (5.2%) had missing admission temperatures, and 300 infants (6.4%) were excluded due to transfer to other hospitals, which could have potentially biased the results.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of thermometry (rectal, axillary or tympanic sites) were not standardized nor consistently recorded in the patient charts. Although there may be a 0.3-0.6C difference between rectal and tympanic or axillary thermometry, 12,13 it is largely impractical and unacceptable to perform rectal thermometry in older pediatric patients, and relatively contraindicated in neutropenic oncology patients, and thus is not the routine practice at our hospital, except in some patients less than three months of age. Blood cultures without collection times comprised 13% of all cultures collected, and their time of receipt at the laboratory was used to approximate the collection time.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…We found that environmental factors did not significantly affect the differences in BT measurements. Similarly, Lantz and Ottosson [16] found that the difference between AT and RT measurements was not influenced by the presence of incubator care. In contrast, Helder et al [17] found that the temperature measurement differences in infants cared for in an incubator were more significant than those in infants cared for in a crib.…”
Section: Discussionmentioning
confidence: 83%
“…This group also found that the difference seemed to increase with increasing postnatal age. Lantz and Ottosson [16] also compared temperature measurements from the axilla and rectum in infants, and found that infants aged <37, 37-42, and >42 weeks had higher RT measurements by 0.33°C, 0.43°C, and 0.48°C, respectively. Hence, the measurement of AT should not replace the gold standard RT, though it may be useful for preterm infants less than 32 weeks, while recognizing its clinical limitations.…”
Section: Discussionmentioning
confidence: 99%